Physicochemical Properties and Metal Ions in Water and Sediment of the Dhaleshwari River - Islam, Md Mazharul; Bhuiyan, Md Hossan Sohid Shoraoardy; Islam, Rakibul; Shoeb, Mohammad; Mamun, Md Iqbal Rouf; Rahman, Md Hafizur (Dhaka University Journal of Science, 2021)
This study was aimed to measure sediment and water quality parameter such as moisture and ash content, pH, TOC, TSS, BOD, TOC, DO, Electrical Conductivity (EC) and Na, K, Ca and Cr metal ions from Dhaleshwari River close to the Savar Tannery Estate (STE). The moisture and ash content of sediments were 23.45-31.42% and 2.09-5.80%, respectively. The pHs of sediment and water samples were 5.20-6.21 and 7.68-8.03, respectively. The average of Ca-hardness, DO and BOD in water were 885.9±88.8, 1.80±0.10 and 16.70± 1.43 mg/L, respectively. The EC of the sediment and water were 24.60-374.00 μS/cm and 32.80-39.50 mS/cm, respectively. The amount of TOC in sediment and water samples were 1.29-3.25g/100g and 2.28-2.70 mg/kg which are very low indicating the fewer amounts of plant and animal residues and sediment biota. TSS in water was 776-936 mg/L which is higher than the permissible limit (600 mg/kg). The Cr content was determined by AAS which implies that the sediment has significantly higher Cr content (38.78-681.62 mg/kg) compared to water (< 0.005 mg/L). The amount of Na and Ca ions were 26.81-45.00 and 16.04-27.36 mg/L, respectively while K ion was very negligible in water. Dhaka Univ. J. Sci. 69(1): 37-42, 2021 (January)